LEGAL INTERPRETATION AND ENFORCEMENT OF TRADEMARK AND COMPARATIVE ADVERTISING INFRINGEMENTS IN US AND EU: A TRANSATLANTIC LEGAL PERSPECTIVES - Waqas Younus; Muhammad Saleem Khan; Farheen Zehra (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the complex interplay between trademark infringement and comparative advertisement, focusing on legal frameworks and case law in the United States and the European Union. The study examines pivotal cases, to elucidate how courts balance the protection of trademark rights with the principles of fair competition and free speech. In the U.S., the Lanham Act provides the foundation for addressing trademark infringement and sets the boundaries for lawful comparative advertising. Conversely, the EU’s legal landscape, shaped by directives and the jurisprudence of the European Court of Justice, offers a different approach to these issues. By comparing domestic trends in the U.S. with overseas practices in the EU, this review highlights the nuances and divergences in legal interpretations and enforcement. The analysis aims to provide a comprehensive understanding of how comparative advertising can be both a tool for market competition and a potential source of trademark disputes. Key findings suggest that while both jurisdictions strive to protect consumer interests and brand integrity, their methodologies and legal standards vary significantly.